OECD/NEA STUDY ON THE ECONOMICS AND MARKET OF SMALL REACTORS - ALEXEY LOKHOV; RON CAMERON; VLADISLAV SOZONIUK (Nuclear Engineering and Technology, 2013)
According to the OECD/NEA estimates, nuclear power plants (NPPs), whether with a large reactor or with small modular reactors (SMRs), are competitive with many other electricity generation technologies in a significant number of cases, one of the exceptions being natural gas in the USA with the current level of prices. However, SMRs have particular features and requirements setting conditions for their deployment. This paper presents the preliminary analysis by OECD/NEA of the economics, opportunities, and market for small nuclear reactors.